If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -7)(2y + 5) = 0 Reorder the terms: (-7 + y)(2y + 5) = 0 Reorder the terms: (-7 + y)(5 + 2y) = 0 Multiply (-7 + y) * (5 + 2y) (-7(5 + 2y) + y(5 + 2y)) = 0 ((5 * -7 + 2y * -7) + y(5 + 2y)) = 0 ((-35 + -14y) + y(5 + 2y)) = 0 (-35 + -14y + (5 * y + 2y * y)) = 0 (-35 + -14y + (5y + 2y2)) = 0 Combine like terms: -14y + 5y = -9y (-35 + -9y + 2y2) = 0 Solving -35 + -9y + 2y2 = 0 Solving for variable 'y'. Factor a trinomial. (-5 + -2y)(7 + -1y) = 0Subproblem 1
Set the factor '(-5 + -2y)' equal to zero and attempt to solve: Simplifying -5 + -2y = 0 Solving -5 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2y = 0 + 5 -2y = 0 + 5 Combine like terms: 0 + 5 = 5 -2y = 5 Divide each side by '-2'. y = -2.5 Simplifying y = -2.5Subproblem 2
Set the factor '(7 + -1y)' equal to zero and attempt to solve: Simplifying 7 + -1y = 0 Solving 7 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 0 + -7 -1y = 0 + -7 Combine like terms: 0 + -7 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7Solution
y = {-2.5, 7}
| 18+4(p-9)=36 | | 1.5x+6=-1.5x+12 | | 4+256x^3=0 | | 2v^2-5=-3v | | 49x^2-56x-159=0 | | s=0.164t-0.65 | | 3/7a=-5 | | 2v^2-5=0 | | 971-((4+788))x(470-454)= | | -d/4=-4.7 | | 2(9x+9)= | | 6r+7+5r+2r=19 | | -1.5z+7=1.5z+1 | | 2x^2-3xy+4y^2-3=0 | | 2n-13=39 | | X+1=6x+12 | | 7y-28=-19+6y | | 3x+10=9x-12 | | 9b-8-3b+5=21 | | 5s+8-4s= | | 971-4= | | 25n^4-9=0 | | -(8w+5)+3(w-15)= | | C^2+12c+36=0 | | 7y-28=-19+6 | | 6z-8z=-2z-24 | | 5-11w=7(5-2w) | | -8x+10=-25 | | 5.25x+6.5*4y=906.25 | | 2m^2*2m^2= | | 6x^4-x^2-5=0 | | 3(4v-8)=24+4v |